2D THz Optoelectronics. Issue 3 (9th December 2020) - Mittendorff, Martin; Winnerl, Stephan; Murphy, Thomas E.
Abstract: The terahertz (THz) region of the electromagnetic spectrum spans the gap between optics and electronics and has historically suffered from a paucity of optoelectronic devices, in large part because of inadequate optical materials that function in this spectral range. 2D materials, including graphene and a growing family of related van der Waals materials, have been shown to exhibit unusual optical and electrical properties that can enable diverse new applications in the THz regime. In this review, some of the unusual properties of 2D materials that make them promising for THz applications are explained, the recent work in the field of 2D THz optoelectronics is summarized, and the challenges and opportunities that await this promising new field are outlined. Abstract : Atomically thin materials like graphene and related van der Waals materials have unusual optical, thermal, and electrical properties in the far‐infrared or terahertz spectral regime. This review article summarizes recent work in the burgeoning field of 2D THz optoelectronics, and explains some of the properties of 2D materials that make them especially useful in this regime.